Iterative composition, coding and pedagogy: A case study in live coding with EarSketch. Issue 1 (1st May 2016) - Freeman, Jason; Magerko, Brian
Pervasive definitions of live coding in music focus on the simultaneous modification and execution of code in a live performance setting where a performer shares his screen with the audience. This article considers a role for live coding that does not focus on live performance but rather on educational contexts. After briefly discussing an iterative model for both musical composition and coding and the potential roles of live coding within this model, the article introduces EarSketch, a learning environment for computer science and music technology that enables students to write Python or JavaScript code to algorithmically generate loop-based music within a digital audio workstation (DAW) workflow. It discusses the impact of code execution time on the learning environment, explains the environment's current support for live coding and discusses the next steps and challenges involved in implementing additional support for live coding in the curriculum and the software environment.